An Assesment of the Malaysian Government Policies to Promote Foreign Direct Investment - Asrar, Omar (1996)
Experiences of most developing countries show that the initial stage of development has to be engineered by the government. In the case of Malaysia, state-managed policy of the “structuralist approach” has become a yardstick for its development. Government in Malaysia work hand in hand with private sectors to accelerate the pace of industrialisation embodied in the Malaysia’s “Vision 2020”. This objective cannot be fulfilled without any contribution from foreign direct investment (FDI) and Malaysian economic experience has proven that FDI is vital for its development. This in part, indicates how vulnerable Malaysia is to the trends at international level. However, the country’s heavy reliance on FDI is not the sole choice of the Malaysian Government, nor does the decision of the capital-exporting countries, but the real mechanism which determines this is the market power. In this sense, the ‘wave’ of FDI is not a phenomenon in Malaysia only, but also to other part of the world, especially the ASEAN countries. In fact, Malaysia was not the first to promote FDI in this region, but it was rather a follower of this policy that proved successful in its neighbouring countries. Looking at these issues this paper examines the policies approached by the Malaysian Government in its different phases of development from three different views of development economics (neo-classical, dependency and structuralist).